A Randomized Control Trial Of Anti-Inflammatory Regional Hypothermia On Urinary Continence During Robot-Assisted Radical Prostatectomy. Issue 1 (December 2018) - Huynh, Linda; Skarecky, Douglas; Porter, James; Wagner, Christian; Witt, Jorn; Wilson, Timothy; Lau, Clayton; Ahlering, Thomas
Abstract The present study seeks to present a single-blind, randomized control trial of a hypothermic anti-inflammatory device, the endorectal cooling balloon (ECB), to assess whether regional hypothermia could improve 90-day and time to pad-free continence following robot-assisted radical prostatectomy (RARP). Five high-volume surgeons at three institutions had patients randomized (1:1) to regional hypothermia with ECB versus control. Patients were blinded to device use, as it was inserted and removed intraoperatively. Knowledge of device use was restricted to the operating room personnel only; recovery room and ward nursing staff were not informed of device use and instructed to indicate such if a patient inquired. An independent and blinded data acquisition contractor assessed outcomes via components of the EPIC and IPSS. The primary outcome was categorical pad-free continence at 90-days and the secondary outcome was a Kaplan-Meier time-to pad-free continence at 90 days. 100 hypothermia and 99 control patients were included. The primary outcome of 90-day pad-free continence was 50.0% (27.8–70.0%) in the hypothermia group versus 59.2% (33.3–78.6%) in the control (p = 0.194). The secondary outcome of Kaplan Meier analysis for time to 90-day continence was not statistically significant. At one year, there were also no statistically significant differences in continence recovery. Post-hoc analysis revealed a trend towards improvement in continence in one of three sites. Overall, the trial demonstrated no benefit to regional hypothermia either in our primary or secondary outcomes. It is suggested that surgical technique and prevention of surgical trauma may be more advantageous to improving continence recovery.